Investigation of Endogenous Retrovirus Sequences in the Neighborhood of Genes Up-regulated in a Neuroblastoma Model after Treatment with Hypoxia-Mimetic Cobalt Chloride - Brütting, Christine; Narasimhan, Harini; Hoffmann, Frank; Kornhuber, Malte E.; Staege, Martin S.; Emmer, Alexander (Frontiers in Microbiology, 2018)
Abstract Human endogenous retroviruses have been found to be associated with different diseases, e.g. multiple sclerosis. Most human endogenous retroviruses integrated in our genome are not competent to replicate and these sequences are presumably silent. However, transcription of human endogenous retroviruses can be reactivated e.g. by hypoxia. Interestingly, multiple sclerosis has been linked to hypoxia since decades. As some patterns of demyelination are similar to white matter ischemia, hypoxic damage is discussed. Therefore, we are interested in the association between hypoxia and endogenous retroviruses. As a model, we used human SH-SY5Y neuroblastoma cells after treatment with the hypoxia-mimetic cobalt chloride and analyzed differences in the gene expression profiles in comparison to untreated cells. The vicinity of up-regulated genes was scanned for endogenous retrovirus-derived sequences. Five genes were found to be strongly up-regulated in SH-SY5Y cells after treatment with cobalt chloride: clusterin, glutathione peroxidase 3, insulin-like growth factor 2, solute carrier family 7 member 11, and neural precursor cell expressed developmentally down-regulated protein 9. In the vicinity of these genes we identified large (> 1,000 bp) open reading frames. All of these open reading frames showed similarities to proteins from retro-transcribing viruses. We found the highest homology (93 %) between retrovirus envelope sequences and a sequence in the vicinity of neural precursor cell expressed developmentally down-regulated protein 9. This sequence encodes the human ERV group FRD member 1, the encoded protein product is called syncytin 2. Transfection of syncytin 2 into the well characterized Ewing sarcoma cell line A673 was not able to modulate the low immunostimulatory activity of this cell line. Future research is needed to determine whether the identified genes and the human endogenous retrovirus group FRD member 1 might play a role in the etiology of multiple sclerosis.